Đào tạo, bồi dưỡng đội ngũ nhà giáo và cán bộ quản lí giáo dục: Nghiên cứu tại Trường Đại học Khoa học - Đại học Thái Nguyên - Bùi Trọng Tài, Bùi Trọng Tài; Bế Hồng Cúc, Bế Hồng Cúc (Tạp chí Giáo dục, 2026)
In response to the demands of higher education reform and the refinement of policies on teachers, higher education institutions need to improve the quality of professional development and training for lecturers and educational administrators to meet competency standards and requirements for international integration. This study investigates and evaluates the current status of professional development and training for teachers and educational managers at the University of Sciences – Thai Nguyen University during 2018–2025 (survey sample: 161). The findings indicate that, despite certain achievements, several limitations remain: some lecturers are not proactive in professional development; foreign-language training/international integration and support mechanisms for young staff are still limited; strong research groups have not been clearly established; and training needs vary across target groups, with prominent priorities including university governance, modern teaching methods, the application of digital technologies/AI, and international publication capacity. Accordingly, the paper recommends shifting from adhoc training to a competency- and job-position–based approach, aligning training with professional goals/KPIs, prioritizing digital–AI competencies and foreign languages, and establishing support mechanisms for young staff while developing strong research groups to ensure sustainable impact.